A Case Study of Chinese Citrus Fly (Bactrocera minax Enderlin) (Diptera: Tephritidae) Pupae in Sindhuli District, Nepal - Thapaliya, R.; Adhikari, D.; Bhattarai, A.M. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.